Intensification: A key strategy to achieve great animal and environmental beef cattle production sustainability in Brachiaria grasslands - da Silva Cardoso, Abmael [UNESP]; Barbero, Rondineli Pavezzi; Romanzini, Eliéder Prates [UNESP]; Teobaldo, Ronyatta Weich [UNESP]; Ongaratto, Fernando [UNESP]; da Rocha Fernandes, Marcia Helena Machado [UNESP]; Ruggieri, Ana Cláudia [UNESP]; Reis, Ricardo Andrade [UNESP] (MDPI, 2020)
Intensification of tropical grassland can be a strategy to increase beef production, but methods for achieving this should maintain or reduce its environmental impact and should not compromise future food-producing capacity. The objective of this review was to discuss the aspects of grassland management, animal supplementation, the environment, and the socioeconomics of grassland intensification. Reducing environmental impact in the form of, for example, greenhouse gas (GHG) emissions is particularly important in Brazil, which is the second-largest beef producer in the world. Most Brazilian pastures, however, are degraded, representing a considerable opportunity for the mitigation and increase of beef-cattle production, and consequently increasing global protein supply. Moreover, in Brazil, forage production is necessary for seasonal feeding strategies that maintain animal performance during periods of forage scarcity. There are many options to achieve this objective that can be adopted alone or in association. These options include improving grassland management, pasture fertilization, and animal supplementation. Improving grazing management has the potential to mitigate GHG emissions through the reduction of the intensity of CO2 emissions, as well as the preservation of natural areas by reducing the need for expanding pastureland. Limitations to farmers adopting intensification strategies include cultural aspects and the lack of financial resources and technical assistance.
Keywords: Animal supplementation; Beef cattle; Grazing management; Pasture fertilization; Sustainable intensification